(untitled) (Heródoto: Revista do Grupo de Estudos e Pesquisas sobre a Antiguidade Clássica e suas Conexões Afro-asiáticas, 2019)
Economy and Society, one of the most influential oeuvres of the early twentieth century, with impact in several branches of the Human Sciences, has in one of its parts a text of particular interest to researchers of Ancient History, the Typology of Cities. Although Max Weber’s significant aims in composing his text were, blatantly, to evaluate the contemporary world, the density of the Weberian text, the fruit of a unique erudition, revealed an in-depth and singular analysis of the ancient Greek city. The purpose of this article is to analyze Weber’s interpretive choices, in the light of historiographical criticism and a careful analysis of the Typology, in articular as regards the ideal types which he made to understand the city of the ancient Greeks.